Anatomical Reattachment of the TFCC to the Ulnar Fovea Using an ECU Half-Slip - Nakamura, Toshiyasu (Journal of Wrist Surgery, 2015)
Background Since 1998, we treated 25 wrists with foveal detachment of the triangular fibrocartilage complex (TFCC) by our original reattachment technique using a half-slip of the extensor carpi ulnaris (ECU) tendon with a very small titanium interference screw. We examine the clinical outcome of this procedure with a minimum of 2 years follow-up.Patients and Methods There were 25 wrists of 24 patients (16 right, 7 left, 1 bilateral, mean age, 34.8 years) with a minimum follow-up of 2 years (range 2–7 years, average 3.1). There was a neutral ulnar variance in 19 wrists and positive in 6. In the positive-variance wrists, an ulnar shortening was performed to prevent ulnar abutment before the reattachment. The diagnosis of a TFCC injury was done by arthrogram, magnetic resonance imaging (MRI), and distal radioulnar (DRUJ) arthroscopy. The clinical outcome was evaluated using our original DRUJ evaluating system.Technique A distally based ECU half-slip was harvested, introduced into the TFCC, sutured to the remnant of the TFCC, and pulled out through a 2.5-mm bone tunnel at the center of the fovea. The ECU half-slip was subsequently anchored to the ulnar fovea with a small titanium interference screw.Results At the final follow-up, 21 wrists had no pain, 3 wrists indicated mild pain, and 1 wrist severe pain. One patient had a loss of supination by 30 degrees. The DRUJ was stable in 22 wrists, moderately unstable in 2 wrists, and severely unstable in 1 wrist. There were 21 excellent, 2 good, 1 fair, and 1 poor results.Conclusions Anatomic reattachment of the TFCC to the ulnar fovea using an ECU half-slip tendon is a promising procedure. This technique is effective for severe DRUJ instability due to chronic foveal avulsion of the TFCC.
Keywords: reattachment; triangular fibrocartilage complex; extensor carpi ulnaris; foveal avulsion; interference screw